Profiling of REST-Dependent microRNAs Reveals Dynamic Modes of Expression - Gao, Zhengliang; Ding, Peiguo; Hsieh, Jenny (Frontiers in Neuroscience, 2012)
Multipotent neural stem cells (NSCs) possess the ability to self-renew and differentiate into both neurons and glia. However, the detailed mechanisms underlying NSC fate decisions are not well understood. Recent work suggests that the interaction between cell type specific transcription factors and microRNAs (miRNAs) is important as resident neural stem/progenitor cells give rise to functionally mature neurons. Recently, we demonstrated that the transcriptional repressor REST (RE1-silencing transcription factor) is essential to prevent precocious neuronal differentiation and maintain NSC self-renewal in the adult hippocampus. Here we show that REST is required for orchestrating the expression of distinct subsets of miRNAs in primary mouse NSC cultures, a physiologically relevant cell type. Using miRNA array profiling, we identified known REST-regulated miRNA genes, as well as previously uncharacterized REST-dependent miRNAs. Interestingly, in response to proliferation and differentiation stimuli, REST-regulated miRNAs formed distinct clusters and displayed variable expression dynamics. These results suggest that REST functions in a context-dependent manner through its target miRNAs for mediating neuronal production.